Effects of maternal dietary nitrate supplementation during the perinatal period on piglet survival, body weight, and litter uniformity. Issue 1 (7th February 2019) - van den Bosch, Moniek; Wijnen, Jan; van de Linde, Irene B; van Wesel, Ad A M; Melchior, Delphine; Kemp, Bas; Clouard, Caroline; van den Brand, Henry
Abstract: The objective of this study was to evaluate effects of different dosages of dietary nitrate supplementation to sows from d 108 of gestation until d 5 of lactation on reproductive performance of sows and piglet performance from birth until weaning. Dietary nitrate supplementation leads to nitric oxide (NO) formation that can potentially increase blood flow to the fetuses (by the vasodilative effect of NO), leading to a decrease in the loss of potential viable piglets in the form of stillbirth and preweaning mortality. Three hundred and five gilts and sows were allocated to one of six diets from d 108 of gestation until d 5 of lactation, containing 0.00% (Control), 0.03%, 0.06%, 0.09%, 0.12%, or 0.15% of dietary nitrate. The source of nitrate used was calcium nitrate double salt. Calcium levels were kept the same among diets by using limestone. Gilts and sows were weighed and backfat was measured at arrival to the farrowing room (d 108 of gestation) and at weaning (d 27 of age). Data included number of piglets born alive, born dead, and weaned, as well as individual piglet weights at d 0, 72 h of age and weaning. Preweaning mortality was determined throughout lactation. Body weight d 0 ( P = 0.04) as well as BW at 72 h of age ( P < 0.01) increased linearly with increasing dosages of nitrate in the maternal diet. Litter uniformity (SD) at birth was not affected by maternal nitrate supplementation level ( P > 0.10), but tended to be higher at 72 h of age in the control treatment than in all nitrate-supplemented treatments ( P = 0.07), and SD decreased linearly (increased uniformity) at weaning with increasing dosages of nitrate ( P = 0.05). BW at weaning ( P > 0.05) and average daily gain of piglets during lactation ( P > 0.05) were not affected by maternal nitrate supplementation. A tendency for a quadratic effect ( P = 0.10) of the dosage of maternal dietary nitrate was found on preweaning mortality of piglets with the lowest level of mortality found at 0.09% to 0.12% of maternal nitrate supplementation. We conclude that the use of nitrate in the maternal diet of sows during the perinatal period might stimulate preweaning piglet vitality. Exact mode of action and optimal dose of nitrate still need to be elucidated.